Bagaimana model problem based learning dapat meningkatkan kemampuan pemecahan masalah matematis? - Salsabila, Hilma; Putra, Harry Dwi; Yuspriyati, Devi Nurul (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This research aims to determine the increase in students mathematical peoblem solving abilities after receiving the problem based learning model. The research method used wa a quasi-experimental method with a nonequivalent control group research design. The population of this study was all students of class VIII MTsN 3 Bandung Barat consisting of four classes. The sample for this research was class VIII C students as the control class applying the normal learning model and class VIII A students as the experimental class applying the problem based learning model. The data obtained was then analyzed quantitatively using the difference between two means test. The process off analizing data involves calculating the average pre-test and post-test scores, the normality test, data with normal distribution continues with the homgeneity test and finally teh t9test. The research result show that there is an increase in students mathematical problem solving abilities after using the problem based learning model.